Analisis Perilaku Konsumen Produk Fashion Local Brand Erigo dalam Memutuskan Pembelian Online melalui E-commerce Shopee - Muhammad Ruslan Zamzami Fahmi; Winarto; Herman (Journal Of Accounting and Business, 2023)
In this online and digital world, shopping can also be done online, such as at Shopee. As we already know, along with the development of technology and information, nowadays many online shops have sprung up in various groups, from teenagers to adults. The business sector currently experiencing intense competition is the fashion business sector, one of which is the local brand Erigo. This research uses descriptive research with qualitative methods using a case study approach that explains phenomena through data collection without prioritizing population size or sampling. to get depth data. The research subjects consisted of five Adm study program students. Business Faculty of Social and Political Sciences, Hang Tuah University, Surabaya. Consumer behavior refers to the purchase decision process which consists of five stages, namely problem recognition, information search, alternative evaluation, purchase decision, and post- purchase behavior. Therefore, the decision making made by some students looks different. Even so, all their needs and desires to get Erigo brand products are still fulfilled by choosing shopee to make purchase transactions  because transactions are more  convenient, complete information,  easier searching, more affordable prices, more flexible time and good consumer confidence. Meanwhile, the consumer's process of deciding to purchase Erigo products online is based on reviews, prices, ratings, as well as the existence of flash sales programs, extra free shipping and discounts. On the other hand, the trust of the informants remains loyal in buying Erigo products using Shopee involving friends and needs related to fashion.